Hubungan Pergaulan Teman Sebaya dengan Prestasi Belajar Siswa Kelas IV SD - Rukayah Rukayah; marliana marliana; sidrah afriani Rahman (Universtas Negeri Makassar, 2022)
The problem in this study is that grade IV students have a high intensity of meeting with friends because most students have a distance of residence that is not far from one another. So that students tend to spend time gathering together in a place where there is wifi that makes it easier for them to play online gamesand access various sites that are still not suitable for the development of students' ages. Activities carried out by these students, of course, can hinder the learning process. This research is a quantitative research with correlational type which aims to determine the relationship between peers and the learning achievement of fourth graders of SD Cluster IV. The results of the study show that there is a significant relationship between peer association and student achievement fourth grade Cluster IV with a value of t arithmetic (3.794) is greater (>) than t table (1.66757) which means H0 Â is rejected and H1 is accepted. Based on the analysis of the data, it can be concluded that peer association can affect student achievement. So, the better the peer association carried out by students, the better the learning achievement obtained by students. From these conclusions, the impact resulting from this study is known that good peer relationships will improve student achievement.